2014
DOI: 10.1111/psyp.12378
|View full text |Cite
|
Sign up to set email alerts
|

ERP and pupil responses to deviance in an oddball paradigm

Abstract: We investigated the relationship between, and functional significance of, P300, novelty P3, and the pupil dilation response (PDR). Subjects categorized stimuli including (a) words of a frequent category, (b) words of an infrequent category (14%), and (c) pictures of the frequent category ("novels"; 14%). The P300 and novelty P3 were uncorrelated with the PDR and differed in their response to experimental manipulation. Therefore, although the three physiological responses often co-occur, they appear to each man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
92
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 86 publications
14
92
1
Order By: Relevance
“…In humans, it has been challenging to assess LC activity directly on a trial-by-trial basis, but pupil dilation has been used as a proxy measure, as phasic LC stimulation leads to pupil dilation (Joshi et al, 2015;Reimer et al, 2016). Indeed, human studies indicate that oddball items produce greater pupil dilation than do frequent items (Gilzenrat et al, 2010;Kamp & Donchin, 2015;Murphy, Robertson, Balsters, & O'Connell, 2011). Furthermore, pupil activity during an oddball task is associated with blood-oxygen-level dependent (BOLD) activity in a dorsal pontine region overlapping with the location of the LC (Murphy et al, 2014).…”
Section: Pupillometry As An Indirect Marker Of Lc Activitymentioning
confidence: 99%
“…In humans, it has been challenging to assess LC activity directly on a trial-by-trial basis, but pupil dilation has been used as a proxy measure, as phasic LC stimulation leads to pupil dilation (Joshi et al, 2015;Reimer et al, 2016). Indeed, human studies indicate that oddball items produce greater pupil dilation than do frequent items (Gilzenrat et al, 2010;Kamp & Donchin, 2015;Murphy, Robertson, Balsters, & O'Connell, 2011). Furthermore, pupil activity during an oddball task is associated with blood-oxygen-level dependent (BOLD) activity in a dorsal pontine region overlapping with the location of the LC (Murphy et al, 2014).…”
Section: Pupillometry As An Indirect Marker Of Lc Activitymentioning
confidence: 99%
“…These isolates also elicit a P300 (Donchin, 1981;Sutton, Braren, Zubin, & John, 1965). In conditions where a behavioral Von Restorff effect was observed, larger P300 amplitudes were elicited by physically deviant isolates that were subsequently recalled, compared to the P300 elicited by isolates that were not subsequently recalled (Fabiani & Donchin, 1995;Fabiani, Karis, & Donchin, 1990;Kamp, Brumback, & Donchin, 2013;Kamp & Donchin, 2015;Kamp, Forester, Murphy, Brumback, & Donchin, 2012;Karis et al, 1984). The P300 subsequent memory effects can thus be used to index the interaction of distinctiveness with episodic encoding: If emotionally charged words are better recalled because they stand out, the behavioral enhancement should be accompanied by a P300, which in turn exhibits a subsequent memory effect.…”
Section: Erp Components That Index Distinctiveness and Semantic Relatmentioning
confidence: 99%
“…In a recent oddball study, comodulation of the PDR response and the early-and late-P3a have been reported: both were enhanced in concert by high-arousing negative novel sounds compared to lowarousing neutral novel sounds (Widmann et al, 2018). However in another oddball study, at the single trial level, P3a did not correlate with the PDR amplitude (Kamp and Donchin, 2015). In oddball studies, a tendency towards a larger P3a has been observed in trials in which a SCR has been elicited (Lyytinen et al, 1992;Marinkovic et al, 2001) but other studies fail to link the SCR to any of the ERPs triggered by novel sounds (Barry et al, 2013;Rushby and Barry, 2009).…”
Section: Relationships Between the Fronto-central P3a And Arousalmentioning
confidence: 88%